Changes in antibiotic use following implementation of a telehealth stewardship pilot program. (7th June 2019) - Wilson, Brigid M.; Banks, Richard E.; Crnich, Christopher J.; Ide, Emma; Viau, Roberto A.; El Chakhtoura, Nadim G.; Jones, Yvonne R.; Cherry, Jason B.; Anderson, Brett A.; Jump, Robin L. P.
Abstract: Starting in 2016, we initiated a pilot tele-antibiotic stewardship program at 2 rural Veterans Affairs medical centers (VAMCs). Antibiotic days of therapy decreased significantly ( P  < .05) in the acute and long-term care units at both intervention sites, suggesting that tele-stewardship can effectively support antibiotic stewardship practices in rural VAMCs.